Acesso livre via repositórios: políticas de instituições brasileiras - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2012)
This is a documental descriptive research intending to analyze the institutional policies for creation and data insertion in repositories of Brazilian universities and research institutions. A research was performed in the ROAR to identify the Brazilian repositories and in the ROARMAP to check the policies registered by Brazilian institutions. Among the 100 Brazilian institutional repositories registered in the ROAR, 34 meet the inclusion criteria, but from this group only three institutions have registered their policies with the ROARMAP: Rio Grande do Sul Federal University (UFRGS), Rio Grande Federal University (FURG) and São Paulo University (USP). The latter was not analyzed given that its policies refer only to thesis and dissertations. The policies analyzed in this study recommend the deposit of scientific publications with peer review (scientific journal papers, conference communications); making the metadata available in open access, respecting the embargo period when required; and incentive to the author to keep the copyright of his/her works. It can be inferred that the policies of UFRGS and FURG were well succeeded, given that their repositories are the first and third, respectively, in the Brazilian ranking on IR records.
Keywords: Acesso livre; Repositórios institucionais; Políticas institucionais; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO